Genome-Wide Analysis of the Polygalacturonase Gene Family in Macadamia and Identification of Members Involved in Fruit Abscission - Yu-Chong Fei; Yi Mo; Jiajing Xu; Kai Lin; Liang Tao; Xiyong He; Meng Li; Zeng-Fu Xu (Plants)
Severe physiological fruit abscission significantly limits yield potential in macadamia. Polygalacturonase (PG), a key hydrolytic enzyme in pectin degradation, plays a critical role in fruit abscission. However, in the macadamia genome, the PG gene family and the members involved in fruit abscission remain poorly understood. In this study, 56 PG gene family members, which were unevenly distributed across 13 of the 14 chromosomes, were identified in the macadamia genome. Phylogenetic analysis clustered these genes into seven clades, with most members found in clades D and E. The MiPGs contained 3–11 exons and 2–10 introns, and except for those in clades E and G, most contained conserved domains I–IV and were predicted to be localized exclusively to the cell membrane. MiPG promoter analysis revealed numerous light-, phytohormone-, and stress-responsive cis-elements. Expression profiling during fruit development showed that twelve MiPGs were either undetectable or expressed at low levels in the fruit abscission zone, whereas eight were highly expressed. MiPG9, MiPG37, and MiPG53 were significantly upregulated during abscission induced by a combination of girdling with defoliation and ethephon treatments. Moreover, transient MiPG37 overexpression in lily petals promoted premature abscission, suggesting that this gene plays a pivotal role in macadamia fruit abscission. These findings advance the functional characterization of macadamia PG genes and highlight a subset of candidate genes for further genetic manipulation to improve fruit retention.